The Relationship Between Customer Satisfaction and Perceived Value on Customer Loyalty - Grzegorz BIESOK; Jolanta WYRÓD-WRÓBEL (Communications of International Proceedings, 2022)
This study using structural equation modelling (SEM) investigates the relationship between customer satisfaction and perceived value on customer loyalty. The model was tested using JASP program. Cronbach’s α and McDonald's ω were used for evaluate the reliability of measurement model. The conceptual model used in the study combines 3 latent variables: perceived value, customer satisfaction and customer loyalty. Each latent variables were described by 3 manifest variables. The survey questionnaires were distributed using snowballing method. The researches was conducted among supermarket customers from southern Poland. Respondents evaluated a total of 35 criteria – manifest variables (describing 6 latent variables). The findings revealed a significant positive correlation between customer satisfaction and loyalty, perceived value and customer satisfaction. The perceived value was found to have significant effect on customer loyalty at a lower level of significance than customer satisfaction.
Keywords: customer satisfaction; loyalty; perceived value; supermarket